The Technique for Teaching Spelling Word to SEPAMA Cambodian Students - Tri Widarwati, Nunun; Indri Astuti, Purwani; Wijayava, Ratih (SCOPE: Journal of English Language Teaching, 2024)
The research aims to analyze spelling word teaching strategies for SEPAMA Cambodian students in 2022. The problem of research such as what is the technique for teaching spelling word to SEPAMA Cambodian Students. The research method is document analysis and interviews. The respondents of research are two female Students and one male student from Univet Bantara as participant of Teaching Assistance Practice in SEPAMA Cambodia. The result of the research is that the spelling word teaching strategy for SEPAMA Cambodian students is through YouTube video as online media and zoom meetings with the live quiz method. This research found that 90 percent students of SEPAMA Cambodia can spell and write the right answers from quiz. The benefit of this research is for scientific development in the field of English Language Education, especially Spelling Teaching Techniques. Implication of research such as the teacher can use youtube and zoom meeting online for teaching spelling word to SEPAMA Cambodian Students.